Properties of eucalyptus pellita. uf. particleboard / Nur Wafa Amalina Amali - Amali, Nur Wafa Amalina (Faculty of Applied Sciences, Universiti Teknologi MARA, 2018)
This research was carried out to study the properties of homogenous particle from Eucalyptus pellita in relation to press-time and density bounded with urea formaldehyde (UF). There are several fixed parameters used like 340mm x 340mm x 12mm board size, 12% of resin content and heating temperature at 165°c. The particleboards were manufactured with 500kg/m3, 600kg/m3 and 700kg/m3 density of board and 4,5 and 6 minutes press-time. The board were evaluated for bending test (Modulus of Elasticity and Modulus of Rupture), internal bonding (IB), thickness swell (TS) and water absorption (WA) according to Malaysian Standard (MS). Board with higher density and high press-time produced better properties of board. This study found that Eucalyptus pellita can be an alternative new raw material in particleboard production